Is Routine Fortification of Human Milk for Babies in the Neonatal Intensive Care Unit Indicated?. Issue 2 (March 2017) - Spatz, Diane L.
Abstract : Although multi-nutrient fortification of human milk for babies in the neonatal intensive care unit is routine in the United States, a recent Cochrane Review suggests limited benefits. Our breastfeeding expert, Dr. Spatz, offers suggestions for evaluating current practice on human milk fortification.